Unveiling the role of long non-coding RNA MALAT1: a comprehensive review on myocardial infarction - Eshraghi, Reza; Sadati, Sina; Bahrami, Ashkan; Mirjalili, Seyed Reza; Farrokhian, Alireza; Mahjoubin-Tehran, Maryam; Mirzaei, Hamed (Frontiers in Cardiovascular Medicine, 2024)
Myocardial infarction (MI) stands at top global causes of death in developed countries, owing mostly to atherosclerotic plaque growth and endothelial injury-induced reduction in coronary blood flow. While early reperfusion techniques have improved outcomes, long-term treatment continues to be difficult. The function of lncRNAs extends to regulating gene expression in various conditions, both physiological and pathological, such as cardiovascular diseases. The objective of this research is to extensively evaluate the significance of the lncRNA called Metastasis associated lung adenocarcinoma transcript 1 (MALAT1) in the development and management of MI. According to research, MALAT1 is implicated in processes such as autophagy, apoptosis, cell proliferation, and inflammation in the cardiovascular system. This investigation examines recent research examining the effects of MALAT1 on heart function and its potential as a mean of diagnosis and treatment for post- MI complications and ischemic reperfusion injury.